Analysis of circulating DNA and protein biomarkers to predict the clinical activity of regorafenib and assess prognosis in patients with metastatic colorectal cancer: a retrospective, exploratory analysis of the CORRECT trial. Issue 8 (August 2015) - Tabernero, Josep; Lenz, Heinz-Josef; Siena, Salvatore; Sobrero, Alberto; Falcone, Alfredo; Ychou, Marc; Humblet, Yves; Bouché, Olivier; Mineur, Laurent; Barone, Carlo; Adenis, Antoine; Yoshino, Takayuki; et al.
Summary: Background: Tumour mutational status is an important determinant of the response of metastatic colorectal cancer to targeted treatments. However, the genotype of the tissue obtained at the time of diagnosis might not accurately represent tumour genotype after multiple lines of treatment. This retrospective exploratory analysis investigated the clinical activity of regorafenib in biomarker subgroups of the CORRECT study population defined by tumour mutational status or plasma protein levels. Methods: We used BEAMing technology to identify KRAS, PIK3CA, and BRAF mutations in DNA obtained from the plasma of 503 patients with metastatic colorectal cancer who enrolled in the CORRECT trial. We quantified total human genomic DNA isolated from plasma samples for 503 patients using a modified version of human long interspersed nuclear element-1 (LINE-1) quantitive real-time PCR. We also measured the concentration of 15 proteins of interest—angiopoietin 2, interleukin 6, interleukin 8, placental growth factor, soluble TIE-1, soluble VEGFR1, VEGF-A, VEGF-C, VEGF-D, VEGF-A isoform 121, bone morphogenetic protein 7, macrophage colony-stimulating factor, stromal cell-derived factor-1, tissue inhibitor of metalloproteinase 2, and von Willebrand factor—in plasma samples from 611 patients. We did correlative analyses of overall survival and progression-free survival in patient subgroups based on mutational status, circulating DNA concentration, and protein concentrations. The CORRECT trial was registered withClinicalTrials.gov, numberNCT01103323 . Findings: Tumour-associated mutations were readily detected with BEAMing of plasma DNA, with KRAS mutations identified in 349 (69%) of 503 patients, PIK3CA mutations in 84 (17%) of 503 patients, and BRAF mutations in 17 (3%) of 502 patients. We did not do correlative analysis based on BRAF genotype because of the low mutational frequency detected for this gene. Some of the most prevalent individual hot-spot mutations we identified included: KRAS ( KRAS G12D, 116 [28%] of 413 mutations; G12V, 72 [17%]; and G13D, 67 [16%]) and PIK3CA ( PIK3CA E542K, 27 [30%] of 89 mutations; E545K, 37 [42%]; and H1047R, 12 [14%]). 41 (48%) of 86 patients who had received anti-EGFR therapy and whose archival tumour tissue DNA was KRAS wild-type in BEAMing analysis were identified as having KRAS mutations in BEAMing analysis of fresh plasma DNA. Correlative analyses suggest a clinical benefit favouring regorafenib across patient subgroups defined by KRAS and PIK3CA mutational status (progression-free survival with regorafenib vs placebo: hazard ratio [HR] 0·52, 95% CI 0·35–0·76 for KRAS wild-type; HR 0·51, 95% CI 0·40–0·65 for KRAS mutant [ KRAS wild type vs mutant, pinteraction =0·74]; HR 0·50, 95% CI 0·40–0·63 for PIK3CA wild-type; HR 0·54, 95% CI 0·32–0·89 for PIK3CA mutant [ PIK3CA wild-type vs mutant, pinteraction =0·85]) or circulating DNA concentration (progression-free survival with regorafenib vs placebo: HR 0·53, 95% CI 0·40–0·71, for low circulating DNA concentrations; HR 0·52, 95% CI 0·40–0·70, for high circulating DNA concentrations; low vs high circulating DNA, pinteraction =0·601). With the exception of von Willebrand factor, assessed with the median cutoff method, plasma protein concentrations were also not associated with regorafenib activity in terms of progression-free survival. In univariable analyses, the only plasma protein that was associated with overall survival was TIE-1, high concentrations of which were associated with longer overall survival compared with low TIE-1 concentrations. This association was not significant in multivariable analyses. Interpretation: BEAMing of circulating DNA could be a viable approach for non-invasive analysis of tumour genotype in real time and for the identification of potentially clinically relevant mutations that are not detected in archival tissue. Additionally, the results show that regorafenib seems to be consistently associated with a clinical benefit in a range of patient subgroups based on mutational status and protein biomarker concentrations. Funding: Bayer HealthCare Pharmaceuticals.